Electrochemical fluorescence switching from a patternable poly(1,3,4-oxadiazole) thin film - Seo, Seogjae; Kim, Yuna; You, Jungmok; Sarwade, Bhimrao D.; Wadgaonkar, Prakash P.; Menon, Shamal K.; More, Arvind S.; Kim, Eunkyoung (Macromolecular Rapid Communications, 2011)
A highly soluble poly(1,3,4-oxadiazole) (POD) substituted with long alkyl chains was examined for electrochemical fluorescence switching. The high solubility of the polymers enabled a simple fabrication of an electrochemical cell, which showed reversible fluorescence switching between dark (n-doping) and bright (neutral) states with a maximum on/off ratio of 2.5 and a cyclability longer than 1000 cycles. Photochemical cleavage of the oxadiazole in POD allowed photo-patterning of the POD film upon exposure to UV source. The patterned POD films displayed patterned image reversibly under a step potential of +1.8/-1.8V.
Keywords: fluorescence; lithography; Luminescence; photochemistry; switching device

Erratum to: catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V. (Research on Chemical Intermediates, 2018)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone®–KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone–KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine–Oxone as an unprecedented catalyst–oxidant combination.
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides